Halal Certification and Labeling Assistance for Processed Food Products in Negororejo Village, Lumbang District, Probolinggo Regency, Indonesia - Mafazah, Lailatul; Jannah, Nur; Hidayatullah, Nur Luthfi; Widyasari, Raras Ayu; Ferliano, Sendy; Fadlilah, Sinta (Program Studi Pengembangan Masyarakat Islam, 2023)
This research tend to elucidate the role of community service programs in assisting halal certification for local small and medium enterprises in remote villages. This research took place during UIN Sunan Ampel Surabaya students and lecturers’ community service program in Negororejo Village, Lumbang District, Probolinggo Regency, Indonesia. The authors argue that community service programs play an important role in assisting small and medium enterprises to apply for halal certification and labeling for their processed food products. This community service research project was conducted by utilizing the Asset Based Community Development method. The result shows that community service programs played a crucial role in assisting halal product certification and labeling of processed food for Negororejo village’s SMEs. As a result of this program, two SMEs have registered halal certification for their products, which are marning and banana chips. Additionally, three SMEs were also assisted through halal product labeling.